Hepatocellular adenoma initially diagnosed as hepatocellular carcinoma with resistance to proton beam radiotherapy - A case report. (June 2021) - Kanno, Hiroki; Maruyama, Yuichiro; Sato, Toshihiro; Hisaka, Toru; Akagi, Yoshito; Okuda, Koji
Abstract: Introduction and importance: Hepatocellular adenoma (HCA) is a rare liver tumor. We report a case of a radio-resistant liver tumor that was removed surgically and found to be HCA. Case presentation: A 37-year-old Japanese man was incidentally diagnosed with a liver tumor. He had no history of viral hepatitis nor metabolic disorders. MRI revealed a tumor enhancing in arterial phase, followed by washout in late phase, and hypointensity in hepatobiliary phase. A diagnosis of hepatocellular carcinoma (HCC) was made and surgery was advised. However, the patient chose proton beam radiotherapy. Although the tumor initially shrunk, it increased in size thereafter. Therefore, anterior sectionectomy was performed. Histology revealed proliferation of hepatocytes without cytologic atypia. On immunohistochemistry, CRP, SAA, GS, L-FABP, and nuclear expression of β-catenin were positive. A final diagnosis of mixed inflammatory and β-catenin activated HCA was made. Clinical discussion: HCA is associated with obesity. The present case was a slightly obese man without history of viral hepatitis. In such cases, HCA should be considered. In the present case, proton beam radiotherapy was performed for a diagnosis of HCC. However, the tumor was radio-resistant. Conclusion: HCA shows an almost equal male to female ratio in the Asian population. Molecular classification is vital in the management of HCA. HCC and HCA are often difficult to differentiate; tumor biopsy is necessary for patients with atypical imaging findings and in younger patients without underlying liver disease. Since the effectiveness of radiation therapy on HCA has not been reported, surgery should be preferred. Highlights: HCA is more prevalent in women in the western countries, while equal gender distribution in Asian countries Subgroups show different imaging findings. I-HCA, atoll sign; b-HCA, iso-hyperintensity in the hepatobiliary phase In the present case, the tumor showed resistance to radiation